Jaminan Pelaksanaan Pemberian Hak-Hak Istri Pasca Perceraian - Jauhari, Jauhari; Busroh, Firman Freaddy; Khairo, Fatria (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Where the divorce case is carried out by the husband or the application for divorce to the Religious Court to be given a decision stating that the husband and wife relationship between them has been broken with the consideration of the panel of judges that the person concerned cannot return to form a sakinah, mawaddah and rahmah household. Therefore, a new problem arises that the ex-husband does not carry out his obligations, namely not giving the rights of his divorced wife such as the granting of 'iddah rights or mut'ah rights. This research is a library research, that is, the source of the data is library research. The research method used is a juridical normative approach. The result of the research is that in the verdict of the panel of judges the sentence is added